Perception of University Lecturers on the Effectiveness of Remote Learning Technique for Teaching Educational Courses during Covid 19 Pandemic in the North Western Region of Nigeria. - Nasiru Dogondaji Muhammad; Isah Maccido; Aliyu Muhammad Dogondaji (Research Synergy Foundation, 2023)
Abstract This Study investigated Perception of University Lecturers on the Effectiveness of Remote Learning Technique for Teaching Educational Courses during Covid 19 pandemic in the North western Region of Nigeria. The study was guided by three objectives, three research questions and two null hypotheses. Descriptive survey research design was employed in the study. The population of the study were 977 lecturers. Simple random sampling technique was used to select the sample. From the population of 977, samples of 349 lecturers were selected for the study. The instrument used for data collection was adapted. Data collected was analysed using descriptive statistics of mean and standard deviation to answer the research questions and chi-square of inferential statistics was for testing Research hypotheses. The major findings of the study revealed that, lecturers were aware of Remote learning model but they were not utilising Remote learning model in teaching their courses during covid-19 pandemic. Similarly, majority of the lecturers’ encountered different challenges in utilising Remote learning model for teaching where by lack of constant electricity supply is one of the major challenges. Moreover, the findings showed that, there is no significance difference between lecturers’ awareness and unawareness of remote learning.